PROSODIC INTERFERENCE SYSTEM THROUGH THE COGNITIVE MODELING PRISM (Proceedings of Southern Federal University. Philology, 2012)
Fomichenko L.G.Keywords: system, structure, model, modeling, prosody, interference, cognitions, knowledge, information.The article is devoted to the investigation of the prosodic interference system through the cognitive modeling. Some questions referring to the study of the notions such as ‘system’, ‘structure’, ‘model’, ‘code’, ‘modeling within the frame of the prosodic level of the language’ are in the focus of the author’s scientific interest.